The Effect of Organization Culture, Work Discipline, and Communication on Employee Performance in PT Tjikko Sentral Industrial - Michelli Dwi Claudia; Pujiarti Pujiarti (eCo-Buss, 2023)
In this Reseach author want to know, do analyze, and determine the effect of Organization Culture, Work Discipline, and Communication on Employee Performance in PT Tjikko Sental Industrial. In this research, author uses quantitative description method which the data from questionnaire. the result from analyze in this research, the author use the validity test, reliability test, classic assuption test, statistical model testing,t test and F test. From the results of the research that has been done, it shows that the value of Adjusted R Square shows the value of the coefficient of determination (R2) is 0.215 or 215%, that means the ability to provide information between the independent and dependent variables is small by 21.5%, the remaining by 78.5% is the other factors outside of this reserach. Based on the t test result, it showed variable X1 ( Organizational Culture) has a value 3,380 > 1,993 with a signifikan 0,0001 < 0,05 that means H0 is rejected and Ha is accepted, variable X2 ( Work Dicipline) has a value 3,279 > 1,993 with a signifikan 0,002 < 0,05 that means H0 is rejected and Ha is accepted, variable X3 ( Communication) has a value 3,620 > 1,993 with a signifikan 0,001 < 0,05 that means H0 is Rejeceted and Ha is accepted. Based on the t test result, between independent variabel has the independent variable has a partial impact on the dependent variable. Based on Ftest, the result has a value 7.682 > 2.73 with a signifikan value signifikan 0,000 < 0,05 that means H0 is Rejected and Ha is accepted, that means the independent variable has a simultaneous influence on the dependent variable .